(untitled) (Medical Forum Monthly, 2024)
Objectives:To find out effect of smoking on isoniazid metabolism in tuberculosis patients. Study Design:Non-Randomized Clinical Trial study. Place and Duration of Study: This study was conducted at the Gulab Devi Chest Hospital, Lahorefrom September to December 2016. Materials and Methods:40 volunteers were included in this study, who were equally divided in four groups as healthy smokers,healthy non smokers, tuberculosis smokers and tuberculosis non smokers. Collection of blood samples was done after three hours of isoniazid dose (300mg) after overnight fasting to avoid food interactions. Concentration of isoniazid and its metabolites were determined using gas chromatography mass spectrometry test. Results: No statistically significant difference in isoniazid metabolites/isoniazid ratio was established(p value<0.05). This shows that the metabolism of isoniazid by N-acetyltransferase-2 enzyme in healthy and tuberculosis patients remains same in smokers and non smokers Conclusions:This trial proved that metabolism of isoniazid by N-acetyltransferase-2 enzyme is independent of smoking. Isoniazid use should be encouraged and adherence should be made imperative in tuberculosis smoker patients for better outcome of tuberculosis treatment.